2010
DOI: 10.1016/j.cellimm.2009.10.013
|View full text |Cite
|
Sign up to set email alerts
|

RELT induces cellular death in HEK 293 epithelial cells

Abstract: RELT is a recently identified Tumor Necrosis Factor Receptor that posesses two homologues in humans named RELL1 and RELL2. We investigated whether RELT and its homologues could induce cellular death when transiently transfected into HEK 293 epithelial cells. Transfection of RELT family members into HEK 293 epithelial cells induced cell death characterized by rounding and lifting of cells accompanied by DNA fragmentation, characteristics that are consistent with the activation of an apoptotic pathway. Overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…2D) previously shown to function as a negative regulator of DC activation, (Kim et al, 2016) among others (Table S1 and S2). We also found that GAS but not S. aureus induced the downregulation of genes associated with inflammasome activation ( NLRP1B ), regulation of NF-κB ( CARD11 ) and the activation receptor CLEC9a , whereas S. aureus specifically downregulated expression of few genes (10 total), including genes associated with regulation of cell cycle and proliferation (G1/S-Specific Cyclin-E1 CCNE1 and the GTPase Ras family member DIRAS2 ) and survival ( RELL1 ) (Cusick et al, 2010). Of note, the genes encoding the inflammatory cytokines IL-1β ( IL1B ), TNF-α (TNF) and IL12p35 ( IL12A ) were amongst genes upregulated by both S. aureus and GAS, however induction by GAS infection was substantially higher than by S. aureus (Figure 2D).…”
Section: Resultsmentioning
confidence: 86%
“…2D) previously shown to function as a negative regulator of DC activation, (Kim et al, 2016) among others (Table S1 and S2). We also found that GAS but not S. aureus induced the downregulation of genes associated with inflammasome activation ( NLRP1B ), regulation of NF-κB ( CARD11 ) and the activation receptor CLEC9a , whereas S. aureus specifically downregulated expression of few genes (10 total), including genes associated with regulation of cell cycle and proliferation (G1/S-Specific Cyclin-E1 CCNE1 and the GTPase Ras family member DIRAS2 ) and survival ( RELL1 ) (Cusick et al, 2010). Of note, the genes encoding the inflammatory cytokines IL-1β ( IL1B ), TNF-α (TNF) and IL12p35 ( IL12A ) were amongst genes upregulated by both S. aureus and GAS, however induction by GAS infection was substantially higher than by S. aureus (Figure 2D).…”
Section: Resultsmentioning
confidence: 86%
“…293 cell line: of kidney or adrenal gland origin and epithelial or neuronal phenotype? 293 cells have been considered the kidney embryonic epithelial cells (e.g., Ashokkumar et al, 2006;Cusick et al, 2010) or even fibroblasts (e.g., Cooper et al, 1998;Yung et al, 2012) and shown to express markers of a kidney developmental stage between the condensed mesenchyme and epithelial S-shaped body but not markers of the differentiated tubular segments, proximal tubules or collecting ducts (Torban and Goodyer, 1998). Moreover, an ectopic expression of transcription factor paired box gene 2 (PAX2), relevant to an early stage of nephrogenesis, modified vimentin, E-cadherin and Wilms tumor 1 expression in 293 cells in such a manner as it occurs during the mesenchymeepithelium transition of early nephrogenesis in vivo (Torban and Goodyer, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of TRAF2 and a TRAF2 mutant lacking its N-terminal RING finger [19] to influence p38 activation by RELL1 and RELL2 was tested, as TRAF2 is a RELL2 binding protein [10]. Co-expression of the RING mutant with either RELL1 or RELL2 plasmids resulted in significantly less activation of p38 ( P <0.005) in comparison to expression of the individual RELT members alone.…”
Section: Resultsmentioning
confidence: 99%
“…RELT activation of the p38 pathway requires phosphorylation by SPAK [7]. RELT family member overexpression induces cell death in human epithelial cells with features characteristic of an apoptotic pathway despite the absence of a characteristic death domain (DD) in RELT [10]. …”
Section: Introductionmentioning
confidence: 99%